DETEKSI SHORT CIRCUIT PADA INSTALASI LISTRIK RUMAH TINGGAL BERBASIS ARDUINO - Achmad Fauzi; Zuraidah Tharo; Dino Erivianto (Jurnal Nasional Teknologi Komputer, 2025)
This research aims to design and test a prototype short circuit detection system for residential electrical installations based on the Arduino Uno microcontroller. The system employs the ACS712 current sensor to detect current surges and uses a relay module to automatically disconnect only the affected circuit. The test results show that the system can accurately detect short circuits with an average response time of 35 milliseconds. It also provides fault location information through an LCD display, improving the efficiency of technical handling. Sensor calibration indicates acceptable accuracy, with measurement deviation under 7%. This system is effective in enhancing residential electrical safety and minimizing the impact of faults on other circuits